Prediction of the behaviour of copper alloy components under complex loadings by electro-thermomechanical coupled simulations. Issue 8 (23rd May 2020) - Weber, M.; Helm, D.
ABSTRACT: Electronic devices must be served with electric power for different reasons. A robust and reliable electric connectivity is often realised by electric connectors. For its leading properties, precipitation hardened copper alloys are widely used for designing connectors with high level mechanical or conductance properties. However, copper alloys show a characteristic stress relaxation under mechanical or thermal loads. Finite element analysis is a standard method to design and optimise components with respect to reliability and performance. Hence, a material model considering the characteristic of the mechanical properties and allowing for the simulation of time and temperature dependent elasto-viscoplastic material behavior was developed at the Fraunhofer IWM. The parameters of the model were determined using tensile and relaxation test data of a C19010 alloy. The material model is applied to electro-thermomechanical coupled finite element simulations of connectors with different load histories. The goal of the simulations is the analysis of the impact of stress relaxation on the mechanical properties of systems over time. From the numerical results with the new model it is shown, how stress relaxation influences the connector clamping forces or contact pressure, respectively, in dependence with time or temperature. The simulation results documents that stress relaxation has to be taken into account in finite element simulations during the designing process of electrical devices. This paper is part of a Thematic Issue on Copper and its Alloys.